Strategi Pemasaran Media Sosial Bagi UMKM Pengrajin Lencana - ., Zuliyati; Salisa, Naila Rizki; Mulyani, Ulva Rizky; Andriani, Evana; Hidayat , Taufiq (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
The increasing development of technology has an impact on the development of Micro, Small and Medium Enterprises (MSMEs), one of which is the AJ Lencana business owned by Mr. Najib which is in Bacin Village, Kudus. The development of business activities from year to year has increased, but sales are only in the area of Central Java residents. It has not been able to spread to the wider community and the marketing that has been running is very, very limited and there has been no touch of social media in efforts to market the product. The solutions offered by the service team to help several problems faced by partners are, social media strategy training to improve product marketing, helping partners to increase sales, expanding partner markets through online shops so that sales can be wider, not only around Central Java. The aim of the Service Team is to move the rural economy to remain productive and be able to utilize technology to help its business activities, as well as increase the sales turnover of partner business activities by utilizing social media.